Chemical plating method for plating copper on surface of silicon wafer
Through the electroless copper plating method that synergizes BaTiO3 quantum dots, microfluidic channels and ultrasonic laser arrays, the uniformity and adhesion of copper film on the surface of the silicon wafer are solved, and efficient and stable copper film preparation is achieved, with excellent conductivity and corrosion resistance, reducing production costs.
Patent Information
- Application Number
- CN202510706002.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon wafer surface electroless copper plating technology has problems such as insufficient uniformity, low adhesion, poor conductivity and poor corrosion resistance. The traditional method has high cost and poor stability, making it difficult to achieve uniform and dense copper film deposition on large-area silicon wafers.
Using the synergistic effect of BaTiO3 quantum dots, microfluidic channels, pulsed liquid supply system and ultrasonic and laser arrays, a quantum dot array is formed by modifying BaTiO3 quantum dots, combining ultrasonic and laser arrays to assist in electroless copper plating, achieving efficient preparation of copper films.
A copper film with uniform thickness, strong adhesion, good conductivity and excellent corrosion resistance was prepared, which simplified the pretreatment steps, reduced production costs and environmental pollution risks, and improved the efficiency and life of the plating solution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor coating, and in particular to a chemical plating method for copper plating on a silicon wafer surface. Background Art
[0002] With the rapid development of microelectronics technology, the integration density and performance requirements of integrated circuits (ICs) continue to increase. Copper (Cu), due to its excellent conductivity, good electromigration resistance, and relatively low cost, has widely replaced aluminum (Al) as the primary material for interconnects in ultra-large-scale integrated circuits (ULSI). The fabrication of copper interconnects typically requires depositing a copper film on a barrier / seed layer through electroplating or chemical plating.
[0003] Electroless Copper Plating (ECP) is an autocatalytic reaction process that does not require an external power source. It relies on the chemical reaction of a reducing agent in the plating solution to reduce copper ions and deposit them on the catalytically active substrate surface. Compared with electroplating, electroless copper plating has the advantages of simple equipment, good deep plating ability, deposition on non-conductive surfaces, and good plating uniformity. It is particularly suitable for forming copper films on fine patterns with complex three-dimensional structures and high aspect ratios. Therefore, it shows great application potential in advanced packaging, through-silicon vias (TSVs) and next-generation interconnect technologies.
[0004] However, direct electroless copper plating on silicon wafer surfaces faces many challenges. First, silicon wafers themselves do not have catalytic activity, and traditional electroless copper plating usually requires complex pretreatment steps, such as palladium activation. However, the palladium activation process is costly and may introduce pollution. Secondly, traditional electroless copper plating solutions are often less stable, easily decomposed, and have a short service life, which increases production costs and environmental pressures. Existing electroless copper plating technologies have difficulty in achieving highly uniform and dense copper film deposition on large-area silicon wafers, and defects such as holes and microcracks are easily generated in the coating, affecting the electrical properties and reliability of the copper film. The adhesion between the copper film and the silicon substrate or the barrier layer thereon is a key issue. Poor adhesion can cause the copper film to peel off during subsequent processes (such as chemical mechanical polishing (CMP)) or during long-term device operation, resulting in device failure. Summary of the Invention
[0005] The present invention discloses an electroless plating method for copper plating on a silicon wafer surface. Through the synergistic effect of BaTiO3 quantum dots, microfluidic channels, a pulsed liquid supply system, and the assistance of ultrasonic and laser arrays, a chemical plating method has been developed that can efficiently and stably prepare a copper film with uniform thickness, strong adhesion, and excellent conductive properties on the silicon wafer surface. The method can prepare a copper film with uniform thickness, strong adhesion, good conductive properties, and excellent corrosion resistance, solving the technical problems of insufficient copper film uniformity and low adhesion in existing silicon wafer copper plating technologies.
[0006] The present invention protects a chemical plating method for copper plating on the surface of a silicon wafer. The method comprises the following steps: modifying BaTiO3 nanocrystals with a silane coupling agent to prepare quantum dot ink; spin-coating the ink on the surface of a P-type silicon wafer cleaned by RCA to form a quantum dot array; activating the ink in a solution containing copper sulfate and trisodium citrate under the assistance of ultrasound; and then chemically plating copper in an alkaline plating solution containing copper sulfate, disodium ethylenediaminetetraacetic acid and glyoxylic acid under the assistance of ultrasound and laser in a microfluidic reaction chamber. The ink is finally rinsed with deionized water and ethanol and blown dry with nitrogen to obtain a silicon wafer with a copper-plated surface.
[0007] As a further improvement of the present invention, the following steps are included: S1. Preparation of quantum dot ink: BaTiO3 nanocrystals were dispersed in ethanol, (3-aminopropyl)triethoxysilane was added, stirred for reaction, washed, and dried to obtain modified BaTiO3 quantum dots, which were then dispersed in isopropanol, a surfactant was added, and ultrasonication was performed to obtain quantum dot ink; S2. Preparation of quantum dot array: Take a single crystal silicon wafer, perform standard RCA cleaning, apply quantum dot ink to the treated silicon wafer surface by spin coating, and dry it to obtain a quantum dot array; S3. Silicon wafer activation: A silicon wafer with a quantum dot array is fixed in a reaction tank, immersed in an activation solution, and subjected to high-frequency ultrasonic waves to produce an activated silicon wafer. S4. Copper film preparation: The activated silicon wafer is transferred to a reaction chamber, and a plating solution is supplied via a syringe pump. Ultrasonic waves and a laser array are simultaneously applied to continuously electrolessly plate copper to form a copper film. S5. Post-processing: Rinse the silicon wafer with deionized water, then rinse with anhydrous ethanol, and finally blow dry with high-purity nitrogen to obtain a silicon wafer with a copper-plated surface.
[0008] As a further improvement of the present invention, in S1, the average particle size of the BaTiO3 nanocrystals is 50 nm, the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals is 1:10, the stirring reaction is carried out at 60°C for 4 hours, and the drying is carried out at 60°C under vacuum conditions for 2 hours. The concentration of the modified BaTiO3 quantum dots in isopropanol is 0.5 mg / mL, the ultrasonic power is 100 W, and the time is 15 minutes. The surfactant is octylphenol polyoxyethylene ether, and the concentration in isopropanol is 0.01% v / v.
[0009] As a further improvement of the present invention, in said S2, the single crystal silicon wafer is a P-type with a resistivity of 1-10Ω·cm. <100> For single crystal silicon wafers, the amount of quantum dot ink used was 0.2 mL, and drying was performed in an oven at 80°C for 10 minutes.
[0010] As a further improvement of the present invention, it is characterized in that, in S2, the spin coating parameters are 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage.
[0011] As a further improvement of the present invention, it is characterized in that, in S2, the standard RCA cleaning method includes: SC-1 cleaning, SC-2 cleaning, and hydrogen peroxide treatment; The SC-1 cleaning solution composition is NH4OH:H2O2:H2O=1:1:5, and the cleaning is carried out at 70-80°C for 10 minutes; The SC-2 cleaning solution composition is HCl:H2O2:H2O=1:1:6, and the cleaning is carried out at 70-80°C for 10 minutes; The hydrogen peroxide treatment uses a 10% hydrogen peroxide aqueous solution at 80° C. for 30 minutes.
[0012] As a further improvement of the present invention, in S3, the temperature of the activation solution is maintained at 25°C, the frequency of the ultrasonic transducer is 1.0 MHz, and the sound intensity is 0.5 W / cm 2 , ultrasonic treatment time was 15 min; The activation solution components include copper sulfate and trisodium citrate, wherein the concentration of copper sulfate is 0.01M, the concentration of trisodium citrate is 0.05M, and the pH value is 4.8-5.2.
[0013] As a further improvement of the present invention, in S4, the reaction temperature is 58-62°C, the reaction chamber is provided with a microfluidic channel, the liquid is supplied in a pulsed manner, the pulse width is 0.5 seconds, the pulse interval is 2.0 seconds, the flow rate is 5 mL / min, the frequency of the ultrasound is 40 kHz, the power is 50 W, the wavelength of the laser array is 532 nm, and the laser power density is 50 mW / cm 2 , the chemical copper plating time is 60 minutes.
[0014] As a further improvement of the present invention, in S4, the components of the chemical copper plating solution include copper sulfate, disodium edetate, glyoxylic acid, a stabilizer and a surfactant, wherein the concentration of copper sulfate is 0.08 M, the concentration of disodium edetate is 0.15 M, the pH value is 12.3-12.7, the concentration of glyoxylic acid is 0.10 M, the stabilizer is 2-mercaptobenzothiazole, the concentration is 2 ppm, and the surfactant is polyethylene glycol octylphenyl ether, the concentration is 50 ppm; As a further improvement of the present invention, the present invention specifically comprises the following steps: S1. Preparation of quantum dot ink: BaTiO3 nanocrystals with an average particle size of 50 nm were dispersed in ethanol, and (3-aminopropyl)triethoxysilane was added at a mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals of 1:10. The mixture was stirred at 60°C for 4 hours, washed multiple times with ethanol, and vacuum-dried at 60°C for 2 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were then dispersed in isopropanol to a concentration of 0.5 mg / mL. The surfactant octylphenol polyoxyethylene ether was added to a concentration of 0.01% v / v, and ultrasonicated at 100 W for 15 minutes to prepare quantum dot ink. S2. Preparation of quantum dot array: Take P-type with a resistivity of 1-10Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 10% hydrogen peroxide solution and treated at 80°C for 30 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.2 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage. The wafers were then dried in an 80°C oven for 10 minutes to obtain quantum dot arrays. The standard RCA cleaning method is as follows: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70-80℃ for 10 minutes, rinsing with deionized water; SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70-80℃ for 10 minutes, rinsing with deionized water, and drying with nitrogen; S3. Silicon wafer activation: The silicon wafer with the quantum dot array was fixed in a reaction tank and immersed in the activation solution. The solution temperature was maintained at 25°C. High-frequency ultrasound was applied to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency was 1.0 MHz and the sound intensity was 0.5 W / cm 2 , continue ultrasonic treatment for 15 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.01M, trisodium citrate concentration 0.05M, and the pH is adjusted to 4.8-5.2 with dilute sulfuric acid or dilute sodium hydroxide; S4. Preparation of copper film: Transfer the activated silicon wafer to a reaction chamber with a microfluidic channel at 58-62°C. Pulse the plating solution via a syringe pump with a pulse width of 0.5 s, a pulse interval of 2.0 s, and a flow rate of 5 mL / min. Simultaneously, apply ultrasound and a laser array with an ultrasound frequency of 40 kHz and a power of 50 W. The wavelength of the laser array is 532 nm, and the laser power density is controlled at 50 mW / cm 2 , continuing chemical copper plating for 60 minutes to obtain a copper film; The composition of the electroless copper plating solution is as follows: 0.08M copper sulfate, 0.15M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.3-12.7 with sodium hydroxide, 0.10M glyoxylic acid, 2ppm stabilizer 2-mercaptobenzothiazole, 50ppm surfactant polyethylene glycol octylphenyl ether; S5. Post-processing: After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3 minutes, then rinsed with anhydrous ethanol for 1 minute, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with a copper-plated surface.
[0015] The present invention has the following beneficial effects: (1) The present invention uses modified BaTiO3 quantum dots to assist in chemical copper plating. The surface of the BaTiO3 quantum dots is modified with (3-aminopropyl)triethoxysilane to form rich amino functional groups, which can form complexes with copper ions. At the same time, the local electric field generated by its ferroelectric properties enhances the efficiency of electron transfer, provides highly active nucleation sites for copper ions, and promotes the growth of uniform copper films. Experimental data show that compared with the control example without using BaTiO3 quantum dots, the copper plating process of the present invention can improve the thickness uniformity of the copper film by 49%, improve adhesion by 49%, reduce resistivity by 139%, and improve corrosion resistance by 210%.
[0016] (2) The present invention introduces microfluidic channels and a pulsed liquid supply system. The stable laminar flow characteristics of the microfluidic channels eliminate the concentration gradients and convection disturbances in traditional electroless copper plating, ensuring that the reactants contact the substrate in a precise metered ratio. The pulsed liquid supply system continuously provides fresh reactants in a cyclical "liquid supply-reaction-replacement" mode, avoiding the problems of plating solution aging and self-decomposition. Experiments have shown that compared with a control sample that does not use microfluidic channels and a pulsed liquid supply system, the copper film thickness uniformity of the present invention is improved by 35%, adhesion is improved by 35%, resistivity is reduced by 68%, and corrosion resistance is improved by 150%.
[0017] (3) The present invention combines ultrasonic and laser array-assisted technologies. The ultrasonic cavitation effect promotes bath mixing and reactant diffusion, removing bubbles and impurity particles. The laser array locally increases the reaction temperature through a controllable photothermal effect, reducing the activation energy of the chemical reaction. The synergistic effect of the two produces a multi-physical field coupling effect, significantly improving the quality of the copper film. Experimental data shows that compared with the controllable example without ultrasonic and laser array assistance, the copper film thickness uniformity of the present invention is improved by 24%, adhesion is improved by 25%, resistivity is reduced by 41%, and corrosion resistance is improved by 85%.
[0018] (4) The copper films prepared by the present invention have excellent comprehensive properties: the thickness uniformity coefficient of the copper films of Examples 1-5 is between 93% and 97%; the adhesion index is between 93% and 97%, indicating that the copper films are firmly bonded to the silicon substrate; the resistivity is only 2.28-2.62 μΩ·cm, which is 132% to 152% relative to the resistivity of pure copper, close to the level of pure copper; the corrosion rate over 72 hours is only 0.0016-0.0023 mg / cm 2 h, showing excellent corrosion resistance.
[0019] (5) The present invention simplifies the complex pretreatment steps of traditional chemical copper plating, eliminates the need for expensive palladium activation processes, and reduces production costs and environmental pollution risks. At the same time, through microfluidics and pulsed liquid supply technology, the efficiency and life of the plating solution are improved, waste liquid discharge is reduced, and significant economic and environmental benefits are achieved.
[0020] (6) The method of the present invention is suitable for preparing copper films on fine patterns with complex three-dimensional structures and high aspect ratios, providing a high-performance technical route for advanced packaging, through-silicon vias (TSVs) and new-generation interconnection technologies, and has broad application prospects. DETAILED DESCRIPTION
[0021] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0022] Example 1: A silicon wafer with copper plating on its surface was prepared.
[0023] S1. BaTiO3 nanocrystals with an average particle size of 50 nm were dispersed in ethanol, (3-aminopropyl)triethoxysilane was added, and the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals was 1:10. The mixture was stirred and reacted at 60°C for 4 hours, washed with ethanol several times, and vacuum dried at 60°C for 2 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were dispersed in isopropanol to a concentration of 0.5 mg / mL, and a surfactant, octylphenol polyoxyethylene ether, was added to a concentration of 0.01% v / v. The quantum dot ink was prepared by ultrasonication at a power of 100 W for 15 minutes.
[0024] S2, take P type with resistivity of 10Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 10% hydrogen peroxide solution and treated at 80°C for 30 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.2 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage. The wafers were then dried in an 80°C oven for 10 minutes to obtain quantum dot arrays. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, and drying with nitrogen.
[0025] S3. Fix the silicon wafer with quantum dot array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 25°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 1.0 MHz and the sound intensity is 0.5 W / cm 2 , continue ultrasonic treatment for 15 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.01M, trisodium citrate concentration 0.05M, and the pH is adjusted to 5.0 with dilute sulfuric acid or dilute sodium hydroxide.
[0026] S4. At 60°C, the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel. The plating solution was supplied in a pulsed manner through a syringe pump. The pulse parameters were a liquid supply pulse width of 0.5 seconds, a pulse interval of 2.0 seconds, and a flow rate of 5 mL / min. Ultrasonic waves and laser arrays were applied simultaneously. The ultrasonic frequency was 40 kHz and the power was 50 W. The wavelength of the laser array was 532 nm, and the laser power density was controlled at 50 mW / cm 2 , continuing chemical copper plating for 60 minutes to obtain a copper film; The composition of the chemical copper plating solution is: 0.08M copper sulfate, 0.15M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.5 with sodium hydroxide, 0.10M glyoxylic acid, 2ppm stabilizer 2-mercaptobenzothiazole, and 50ppm surfactant polyethylene glycol octylphenyl ether.
[0027] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3 minutes, then rinsed with anhydrous ethanol for 1 minute, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plating on the surface.
[0028] Example 2: A silicon wafer with copper plating on its surface was prepared.
[0029] S1. BaTiO3 nanocrystals with an average particle size of 30 nm were dispersed in methanol, (3-aminopropyl)trimethoxysilane was added, and the mass ratio of (3-aminopropyl)trimethoxysilane to BaTiO3 nanocrystals was 1:8. The mixture was stirred and reacted at 55°C for 3.5 hours. The mixture was washed with methanol several times and vacuum dried at 55°C for 2.5 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were dispersed in acetone to a concentration of 0.6 mg / mL. The surfactant sodium dodecyl sulfate was added to a concentration of 0.012% v / v. The mixture was ultrasonicated at a power of 120 W for 12 minutes to prepare quantum dot ink.
[0030] S2, take P type with resistivity of 5Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 12% hydrogen peroxide solution and treated at 85°C for 25 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.25 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 600 rpm for 12 seconds in the first stage and 3500 rpm for 35 seconds in the second stage. The wafers were then dried in an 85°C oven for 8 minutes to produce quantum dot arrays. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 75-85℃ for 12 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 75-85℃ for 12 minutes, rinsing with deionized water, and drying with nitrogen.
[0031] S3. Fix the silicon wafer with quantum dot array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 28°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 1.2MHz and the sound intensity is 0.6W / cm 2 , continue ultrasonic treatment for 12 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.015M, trisodium citrate concentration 0.06M, and the pH is adjusted to 5.2 with dilute sulfuric acid or dilute sodium hydroxide.
[0032] S4. At 62°C, the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel. The plating solution was supplied in a pulsed manner through a syringe pump. The pulse parameters were a liquid supply pulse width of 0.6 seconds, a pulse interval of 1.8 seconds, and a flow rate of 6 mL / min. Ultrasonic waves and a laser array were applied simultaneously. The ultrasonic frequency was 45 kHz and the power was 60 W. The wavelength of the laser array was 532 nm, and the laser power density was controlled at 60 mW / cm 2 , continuing chemical copper plating for 55 minutes to obtain a copper film; The composition of the chemical copper plating solution is: 0.09M copper sulfate, 0.16M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.7 with sodium hydroxide, 0.12M glyoxylic acid, 2.5ppm stabilizer 2-mercaptobenzothiazole, and 60ppm surfactant polyethylene glycol octylphenyl ether.
[0033] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3.5 minutes, then rinsed with anhydrous ethanol for 1.5 minutes, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plating on the surface.
[0034] Example 3: A silicon wafer with copper plating on its surface was prepared.
[0035] S1. BaTiO3 nanocrystals with an average particle size of 70 nm were dispersed in n-butanol, (3-aminopropyl)triethoxysilane was added, and the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals was 1:12. The mixture was stirred and reacted at 65°C for 4.5 hours, washed with ethanol several times, and vacuum dried at 65°C for 1.5 hours to obtain modified BaTiO3 quantum dots, which were dispersed in isopropanol to a concentration of 0.4 mg / mL. A surfactant, polysorbate 80, was added to a concentration of 0.008% v / v, and ultrasonicated at a power of 90 W for 18 minutes to prepare quantum dot ink.
[0036] S2, take P type with resistivity of 3Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in an 8% hydrogen peroxide solution and treated at 75°C for 35 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.18 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 450 rpm for 8 seconds in the first stage and 2800 rpm for 45 seconds in the second stage. The wafers were then dried in a 75°C oven for 12 minutes to produce quantum dot arrays. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70-80℃ for 8 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70-80℃ for 8 minutes, rinsing with deionized water, and drying with nitrogen.
[0037] S3. Fix the silicon wafer with quantum dot array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 23°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 0.8MHz and the sound intensity is 0.4W / cm 2 , continued ultrasonic treatment for 18 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.008M, trisodium citrate concentration 0.04M, and the pH is adjusted to 4.8 with dilute sulfuric acid or dilute sodium hydroxide.
[0038] S4. At 58°C, the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel. The plating solution was supplied in a pulsed manner through a syringe pump. The pulse parameters were a liquid supply pulse width of 0.4 seconds, a pulse interval of 2.2 seconds, and a flow rate of 4 mL / min. Ultrasonic waves and a laser array were applied simultaneously. The ultrasonic frequency was 35 kHz and the power was 40 W. The wavelength of the laser array was 532 nm, and the laser power density was controlled at 40 mW / cm 2 , continuing chemical copper plating for 65 minutes to obtain a copper film; The composition of the chemical copper plating solution is: 0.07M copper sulfate, 0.14M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.3 with sodium hydroxide, 0.09M glyoxylic acid, 1.5ppm stabilizer 2-mercaptobenzothiazole, and 40ppm surfactant polyethylene glycol octylphenyl ether.
[0039] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 2.5 minutes, then rinsed with anhydrous ethanol for 0.8 minutes, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plated on the surface.
[0040] Example 4: A silicon wafer with copper plating on its surface was prepared.
[0041] S1. BaTiO3 nanocrystals with an average particle size of 40 nm were dispersed in ethanol, (3-aminopropyl)trimethoxysilane was added, and the mass ratio of (3-aminopropyl)trimethoxysilane to BaTiO3 nanocrystals was 1:9. The mixture was stirred and reacted at 58°C for 3.8 hours. The mixture was washed with ethanol several times and vacuum dried at 58°C for 2.2 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were dispersed in n-propanol to a concentration of 0.55 mg / mL. The surfactant hexadecyltrimethylammonium bromide was added to a concentration of 0.011% v / v. The mixture was ultrasonicated at a power of 110 W for 14 minutes to prepare quantum dot ink.
[0042] S2, take P type with resistivity of 7Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in an 11% hydrogen peroxide solution and treated at 82°C for 28 minutes. They were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.22 mL of quantum dot ink was added to the center of the silicon wafer. The spin coating parameters were 550 rpm for 11 seconds in the first stage and 3200 rpm for 42 seconds in the second stage. The wafers were then dried in an 82°C oven for 9 minutes to produce a quantum dot array. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 72-82℃ for 11 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 72-82℃ for 11 minutes, rinsing with deionized water, and drying with nitrogen.
[0043] S3. Fix the silicon wafer with quantum dot array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 26°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 1.1MHz and the sound intensity is 0.55W / cm 2 , ultrasonic treatment was continued for 14 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.012M, trisodium citrate concentration 0.055M, and the pH is adjusted to 5.1 with dilute sulfuric acid or dilute sodium hydroxide.
[0044] S4. At 61°C, the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel. The plating solution was supplied in a pulsed manner through a syringe pump. The pulse parameters were a liquid supply pulse width of 0.55 seconds, a pulse interval of 1.9 seconds, and a flow rate of 5.5 mL / min. Ultrasonic waves and a laser array were applied simultaneously. The ultrasonic frequency was 42 kHz and the power was 55 W. The wavelength of the laser array was 532 nm, and the laser power density was controlled at 55 mW / cm 2 , continuing chemical copper plating for 58 minutes to obtain a copper film; The composition of the chemical copper plating solution is: 0.085M copper sulfate, 0.155M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.6 with sodium hydroxide, 0.11M glyoxylic acid, 2.2ppm stabilizer 2-mercaptobenzothiazole, and 55ppm surfactant polyethylene glycol octylphenyl ether.
[0045] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3.2 minutes, then rinsed with anhydrous ethanol for 1.2 minutes, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plating on the surface.
[0046] Example 5: A silicon wafer with copper plating on its surface was prepared.
[0047] S1. BaTiO3 nanocrystals with an average particle size of 60 nm were dispersed in isopropanol, (3-aminopropyl)triethoxysilane was added, and the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals was 1:11. The mixture was stirred and reacted at 62°C for 4.2 hours, washed with ethanol multiple times, and vacuum dried at 62°C for 1.8 hours to obtain modified BaTiO3 quantum dots, which were dispersed in methanol to a concentration of 0.45 mg / mL. A surfactant, poloxamer 188, was added to a concentration of 0.009% v / v, and ultrasonicated at a power of 105 W for 16 minutes to prepare quantum dot ink.
[0048] S2, take P type with resistivity of 5Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 9% hydrogen peroxide solution and treated at 78°C for 32 minutes. They were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.21 mL of quantum dot ink was added to the center of the silicon wafer. The spin coating parameters were 480 rpm for 9 seconds in the first stage and 2900 rpm for 38 seconds in the second stage. The wafers were then dried in a 78°C oven for 11 minutes to produce quantum dot arrays. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70-80℃ for 9 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70-80℃ for 9 minutes, rinsing with deionized water, and drying with nitrogen.
[0049] S3. Fix the silicon wafer with quantum dot array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 24°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 0.9 MHz and the sound intensity is 0.45 W / cm 2 , ultrasonic treatment was continued for 16 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.009 M, trisodium citrate concentration 0.045 M, and the pH is adjusted to 4.9 with dilute sulfuric acid or dilute sodium hydroxide.
[0050] S4. At 59°C, the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel. The plating solution was supplied in a pulsed manner through a syringe pump. The pulse parameters were a liquid supply pulse width of 0.45 seconds, a pulse interval of 2.1 seconds, and a flow rate of 4.5 mL / min. Ultrasonic waves and laser arrays were applied simultaneously. The ultrasonic frequency was 38 kHz and the power was 45 W. The wavelength of the laser array was 532 nm, and the laser power density was controlled at 45 mW / cm 2 , continuing chemical copper plating for 62 minutes to obtain a copper film; The composition of the chemical copper plating solution is: 0.075M copper sulfate, 0.145M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.4 with sodium hydroxide, 0.095M glyoxylic acid, 1.8ppm stabilizer 2-mercaptobenzothiazole, and 45ppm surfactant polyethylene glycol octylphenyl ether.
[0051] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 2.8 minutes, then rinsed with anhydrous ethanol for 0.9 minutes, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plated on the surface.
[0052] Comparative Example 1: A silicon wafer with copper plating on its surface was prepared. Different from Example 1, in S4, no microfluidic channel and pulsed liquid supply were used during the chemical copper plating, and no ultrasonic wave and laser array assistance were applied.
[0053] S1. BaTiO3 nanocrystals with an average particle size of 50 nm were dispersed in ethanol, (3-aminopropyl)triethoxysilane was added, and the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals was 1:10. The mixture was stirred and reacted at 60°C for 4 hours, washed with ethanol several times, and vacuum dried at 60°C for 2 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were dispersed in isopropanol to a concentration of 0.5 mg / mL, and a surfactant, octylphenol polyoxyethylene ether, was added to a concentration of 0.01% v / v. The quantum dot ink was prepared by ultrasonication at a power of 100 W for 15 minutes.
[0054] S2, take P type with resistivity of 10Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 10% hydrogen peroxide solution and treated at 80°C for 30 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.2 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage. The wafers were then dried in an 80°C oven for 10 minutes to obtain quantum dot arrays. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, and drying with nitrogen.
[0055] S3. Fix the silicon wafer with quantum dot array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 25°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 1.0 MHz and the sound intensity is 0.5 W / cm 2, continue ultrasonic treatment for 15 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.01M, trisodium citrate concentration 0.05M, and the pH is adjusted to 5.0 with dilute sulfuric acid or dilute sodium hydroxide.
[0056] S4. At 60° C., the activated silicon wafer was transferred to a conventional reaction vessel and directly immersed in the plating solution without using a microfluidic channel or a pulsed liquid supply method, and without applying ultrasonic waves or laser array assistance. The electroless copper plating was continued for 60 minutes to produce a copper film. The composition of the chemical copper plating solution is: 0.08M copper sulfate, 0.15M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.5 with sodium hydroxide, 0.10M glyoxylic acid, 2ppm stabilizer 2-mercaptobenzothiazole, and 50ppm surfactant polyethylene glycol octylphenyl ether.
[0057] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3 minutes, then rinsed with anhydrous ethanol for 1 minute, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plating on the surface.
[0058] Comparative Example 2: A silicon wafer with copper plating on its surface was prepared. Compared with Example 1, the activation step in S3 lacked ultrasonic assistance and the chemical copper plating process in S4 lacked laser array assistance.
[0059] S1. BaTiO3 nanocrystals with an average particle size of 50 nm were dispersed in ethanol, (3-aminopropyl)triethoxysilane was added, and the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals was 1:10. The mixture was stirred and reacted at 60°C for 4 hours, washed with ethanol several times, and vacuum dried at 60°C for 2 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were dispersed in isopropanol to a concentration of 0.5 mg / mL, and a surfactant, octylphenol polyoxyethylene ether, was added to a concentration of 0.01% v / v. The quantum dot ink was prepared by ultrasonication at a power of 100 W for 15 minutes.
[0060] S2, take P type with resistivity of 10Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 10% hydrogen peroxide solution and treated at 80°C for 30 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.2 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage. The wafers were then dried in an 80°C oven for 10 minutes to obtain quantum dot arrays. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, and drying with nitrogen.
[0061] S3. Fix the silicon wafer with the quantum dot array in the reaction tank and immerse it in the activation solution. Maintain the solution temperature at 25°C without ultrasonic-assisted activation. Let it stand and soak for 15 minutes to obtain an activated silicon wafer. The activation solution comprises the following components: copper sulfate concentration 0.01M, trisodium citrate concentration 0.05M, and the pH is adjusted to 5.0 with dilute sulfuric acid or dilute sodium hydroxide.
[0062] S4. At 60° C., the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel, and the plating solution was supplied in a pulsed manner by a syringe pump. The pulse parameters were a liquid supply pulse width of 0.5 seconds, a pulse interval of 2.0 seconds, and a flow rate of 5 mL / min. Ultrasonic waves were applied at a frequency of 40 kHz and a power of 50 W, but no laser array was applied for assistance. The electroless copper plating was continued for 60 minutes to produce a copper film. The composition of the chemical copper plating solution is: 0.08M copper sulfate, 0.15M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.5 with sodium hydroxide, 0.10M glyoxylic acid, 2ppm stabilizer 2-mercaptobenzothiazole, and 50ppm surfactant polyethylene glycol octylphenyl ether.
[0063] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3 minutes, then rinsed with anhydrous ethanol for 1 minute, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plating on the surface.
[0064] Comparative Example 3: A silicon wafer with copper plating on its surface was prepared. The difference from Example 1 is that in step S1, the BaTiO3 nanocrystals were replaced with SiO2 nanoparticles.
[0065] S1. Disperse SiO2 nanoparticles (not BaTiO3 nanocrystals) with an average particle size of 50 nm in ethanol, add (3-aminopropyl)triethoxysilane, and the mass ratio of (3-aminopropyl)triethoxysilane to SiO2 nanoparticles is 1:10. Stir and react at 60°C for 4 hours, wash with ethanol several times, and vacuum dry at 60°C for 2 hours to obtain modified SiO2 nanoparticles. Disperse in isopropanol to a concentration of 0.5 mg / mL, add surfactant octylphenol polyoxyethylene ether to a concentration of 0.01% v / v, and ultrasonicate at a power of 100 W for 15 minutes to prepare nanoparticle ink.
[0066] S2, take P type with resistivity of 10Ω·cm <100> A single crystal silicon wafer was used as a silicon wafer and cleaned using a standard RCA cleaning method. The cleaned silicon wafer was placed in a 10% hydrogen peroxide solution and treated at 80°C for 30 minutes. It was then rinsed with deionized water and dried with nitrogen to obtain a treated silicon wafer. Nanoparticle ink was then coated on the treated silicon wafer surface using a spin coating method. 0.2 mL of nanoparticle ink was dropped onto the center of the silicon wafer. The spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage. The wafer was then dried in an 80°C oven for 10 minutes to produce a nanoparticle array. Among them, the standard RCA cleaning method is: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70~80℃ for 10 minutes, rinsing with deionized water, and drying with nitrogen.
[0067] S3. Fix the silicon wafer with the nanoparticle array in the reaction tank and immerse it in the activation solution. The solution temperature is maintained at 25°C. Apply high-frequency ultrasound to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency is 1.0 MHz and the sound intensity is 0.5 W / cm 2 , continue ultrasonic treatment for 15 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.01M, trisodium citrate concentration 0.05M, and the pH is adjusted to 5.0 with dilute sulfuric acid or dilute sodium hydroxide.
[0068] S4. At 60°C, the activated silicon wafer was transferred to a reaction chamber with a microfluidic channel. The plating solution was supplied in a pulsed manner through a syringe pump. The pulse parameters were a liquid supply pulse width of 0.5 seconds, a pulse interval of 2.0 seconds, and a flow rate of 5 mL / min. Ultrasonic waves and laser arrays were applied simultaneously. The ultrasonic frequency was 40 kHz and the power was 50 W. The wavelength of the laser array was 532 nm, and the laser power density was controlled at 50 mW / cm 2 , continuing chemical copper plating for 60 minutes to obtain a copper film; The composition of the chemical copper plating solution is: 0.08M copper sulfate, 0.15M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.5 with sodium hydroxide, 0.10M glyoxylic acid, 2ppm stabilizer 2-mercaptobenzothiazole, and 50ppm surfactant polyethylene glycol octylphenyl ether.
[0069] S5. After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3 minutes, then rinsed with anhydrous ethanol for 1 minute, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with copper plating on the surface.
[0070] Performance testing: The copper-plated silicon wafers prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were used as samples for performance testing.
[0071] Test method 1. Copper film thickness measurement.
[0072] Sample preparation: Cut the copper-plated silicon wafer to be tested into small pieces of 10 mm × 10 mm, and measure 5 different positions of each sample.
[0073] Instrument settings: A step profiler (Dektak XT) was used with the following measurement parameters: tip radius 2 μm, scan length 5000 μm, scan speed 10 μm / s, and applied force 5 mg.
[0074] Measurement steps: a) Carefully sand down a thin line on the sample surface with fine sandpaper to expose the underlying silicon substrate.
[0075] b) Fix the sample on the sample stage of the step analyzer and adjust the level.
[0076] c) Set the scanning path to pass perpendicularly through the grinding line.
[0077] d) Start scanning to obtain the surface profile.
[0078] e) Use software to measure the height difference between the copper film and the substrate, which is the thickness of the copper film.
[0079] f) Repeat the measurement for each sample 5 times and take the average value.
[0080] Test method 2: Copper film uniformity test.
[0081] Sample preparation: Cut the copper-plated silicon wafer to be tested into 25 mm × 25 mm squares.
[0082] Instrument settings: Use a four-probe resistance tester (CMT-SR2000N) with a probe spacing of 1 mm and a test current of 1 mA.
[0083] Measurement steps: a) Place the sample on the test platform.
[0084] b) Set 9 measurement points on the sample surface, distributed in a 3×3 grid.
[0085] c) Perform four-probe measurement at each point and record the sheet resistance value.
[0086] d) Calculate the average sheet resistance and standard deviation of the 9 points.
[0087] e) Uniformity index = standard deviation / average value × 100%. The smaller the value, the better the uniformity.
[0088] Test method 3: Copper film adhesion test.
[0089] Sample preparation: Cut the copper-plated silicon wafer to be tested into 20 mm × 20 mm squares.
[0090] Instrument settings: Use a cross-cut tester (QFH-A), with a tool spacing of 1 mm and a tool hardness of HRC60.
[0091] Measurement steps: a) Use a cross-hatch tester to create a 10 × 10 grid on the sample surface, with a total area of 10 mm × 10 mm.
[0092] b) Use standard tape (3M 600) to stick to the grid surface and gently rub with an eraser to ensure full contact.
[0093] c) Quickly peel off the tape at a 45° angle.
[0094] d) Use an optical microscope to observe and count the number of fallen squares.
[0095] e) Adhesion index = (100-number of fallen squares) / 100×100%. The larger the value, the better the adhesion.
[0096] Test method 4: Copper film conductivity test.
[0097] Sample preparation: Cut the copper-plated silicon wafer to be tested into strips of 5 mm × 30 mm.
[0098] Instrument settings: Use a four-probe resistance tester (CMT-SR2000N) with a probe spacing of 1 mm and a test current range of 0.1–100 mA.
[0099] Measurement steps: a) Fix the sample on the test platform.
[0100] b) Place the four probes perpendicular to the sample surface, ensuring good contact.
[0101] c) Set the test current to 1 mA and record the voltage drop.
[0102] d) Calculate the resistivity according to the formula ρ = πt / ln2·V / I, where t is the film thickness, V is the measured voltage, and I is the test current.
[0103] e) Each sample was measured 5 times and the average value was taken.
[0104] Test method 5: Copper film corrosion resistance test.
[0105] Sample preparation: Cut the copper-plated silicon wafer to be tested into 15 mm × 15 mm squares.
[0106] Preparation of etching solution: 3.5wt% sodium chloride aqueous solution, pH value adjusted to 4.0.
[0107] Measurement steps: a) Record the initial weight of the sample W0.
[0108] b) Immerse the sample in the corrosive solution and let it stand at room temperature (25°C).
[0109] c) Take out the samples after soaking for 24h, 48h and 72h respectively.
[0110] d) Rinse gently with deionized water, clean with anhydrous ethanol, and blow dry with nitrogen.
[0111] e) Record the weight of the sample after corrosion, W1.
[0112] f) Calculate the corrosion rate: Corrosion rate = (W0-W1) / (S×t), where S is the surface area of the sample (cm 2 ), t is the corrosion time (h).
[0113] Test data table Table 1. Copper film thickness data table (μm)
[0114] Table 2. Copper film uniformity test data
[0115] Table 3. Copper film adhesion test data
[0116] Table 4. Copper film conductivity test data
[0117] Table 5. Copper film corrosion resistance test data (72h corrosion rate, mg / cm 2 h)
[0118] Data Analysis As can be seen from Table 1, the copper films prepared in Examples 1-5 of the present invention all have thicknesses between 2.65-3.12 μm, and are uniform in thickness with a standard deviation of only about 0.05 μm. In contrast, the copper film thickness of Comparative Example 1 is only 1.65 μm, which is 42% less than that of Example 1. This is mainly due to the lack of microfluidic channels and pulsed liquid supply systems, resulting in poor fluidity of the plating solution and insufficient renewal of the reaction surface. The copper film thickness of Comparative Example 2 is 2.05 μm, which is 28% less than that of Example 1. This is because the lack of ultrasonic assistance in the activation step and the lack of laser array assistance in the chemical copper plating process result in uneven distribution of catalytic active points. The copper film thickness of Comparative Example 3 is the lowest, only 1.26 μm, which is 56% less than that of Example 1. This is because SiO2 nanoparticles are used instead of BaTiO3 quantum dots, which lack the unique photoelectrocatalytic properties of quantum dots and cannot effectively promote the reduction and deposition of copper ions. These data fully demonstrate the significant effect of BaTiO3 quantum dots, microfluidic channels, pulsed liquid supply systems, and ultrasonic and laser array assistance in the present invention on increasing the thickness of copper films.
[0119] As can be seen from Table 2, the copper film uniformity indexes of Examples 1-5 of the present invention are all between 3.5% and 4.2%, indicating that the copper film deposition is very uniform. In contrast, the uniformity index of Comparative Example 1 is 6.4%, which is 60% higher than that of Example 1, indicating that the lack of the use of microfluidic channels and pulsed liquid supply system will lead to uneven distribution of the plating solution, thereby affecting the uniformity of copper film deposition; the uniformity index of Comparative Example 2 is 5.3%, which is 32.5% higher than that of Example 1, indicating that ultrasonic and laser array assistance can significantly improve the uniformity of copper film deposition; the uniformity index of Comparative Example 3 is as high as 7.7%, which is 92.5% higher than that of Example 1, further demonstrating the key role of BaTiO3 quantum dots in promoting uniform deposition. These data show that the technical solution of the present invention can significantly improve the uniformity of copper film deposition through the synergistic effect of microfluidic channels, pulsed liquid supply system, and ultrasonic and laser array assistance.
[0120] As can be seen from Table 3, the copper film adhesion indexes of Examples 1-5 of the present invention are all between 93% and 97%, indicating that the copper film is firmly bonded to the silicon substrate. In contrast, the adhesion index of Comparative Example 1 is only 62%, 35% lower than that of Example 1, indicating that the microfluidic channel and pulsed liquid supply system play an important role in improving the adhesion of the copper film; the adhesion index of Comparative Example 2 is 71%, 25% lower than that of Example 1, indicating that ultrasound and laser array assistance can significantly enhance the bonding strength between the copper film and the substrate; the adhesion index of Comparative Example 3 is the lowest, only 48%, 49% lower than that of Example 1, which fully demonstrates the key role of BaTiO3 quantum dots in improving the adhesion of the copper film. These data show that the present invention can significantly improve the bonding strength and lifespan of the copper film to the silicon substrate through the synergistic effects of quantum dot assistance, microfluidic channels, pulsed liquid supply, and ultrasound and laser arrays.
[0121] As can be seen from Table 4, the resistivity of the copper films of Examples 1-5 of the present invention is all between 2.28-2.62 μΩ·cm, with a resistivity ratio of 132% to 152% relative to pure copper, which is close to the conductivity of pure copper. In comparison, the resistivity of Comparative Example 1 is 4.12 μΩ·cm, 68% higher than that of Example 1, indicating that the microfluidic channel and pulsed liquid supply system have a significant effect on improving the conductivity of the copper film; the resistivity of Comparative Example 2 is 3.45 μΩ·cm, 41% higher than that of Example 1, indicating that ultrasound and laser array assistance can effectively improve the conductivity of the copper film; the resistivity of Comparative Example 3 is as high as 5.85 μΩ·cm, 139% higher than that of Example 1, which further demonstrates the important role of BaTiO3 quantum dots in improving the conductivity of the copper film. These data show that the copper film produced by the technical solution of the present invention has good conductivity, close to that of pure copper.
[0122] As can be seen from Table 5, the 72-hour corrosion rates of the copper films of Examples 1-5 of the present invention are all between 0.0016 and 0.0023 mg / cm 2 ·h, showing excellent corrosion resistance. In contrast, the corrosion rate of comparative example 1 was 0.0050mg / cm 2 h, which is 150% higher than that of Example 1, indicating that the microfluidic channel and pulse liquid supply system play an important role in improving the corrosion resistance of the copper film; the corrosion rate of Comparative Example 2 is 0.0037 mg / cm 2 h, which is 85% higher than that of Example 1, indicating that ultrasound and laser array assistance can significantly improve the corrosion resistance of the copper film; the corrosion rate of Comparative Example 3 is as high as 0.0062 mg / cm 2h, 210% higher than in Example 1, fully demonstrating the key role of BaTiO3 quantum dots in improving the corrosion resistance of the copper film. These data show that the present invention can significantly improve the corrosion resistance of the copper film through the synergy of quantum dot assistance, microfluidic channels, pulsed liquid supply, and ultrasound and laser arrays.
[0123] In summary, the quantum dot-assisted chemical copper plating method proposed in the present invention can prepare a copper film with uniform thickness, strong adhesion, good conductivity and excellent corrosion resistance through the synergistic effect of BaTiO3 quantum dots, microfluidic channels, pulsed liquid supply system, and ultrasonic and laser array assistance. This method not only improves the efficiency and quality of chemical copper plating, but also provides a new copper interconnection technology route for the manufacture of microelectronic devices.
[0124] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for electroless copper plating on a silicon wafer surface, characterized in that: The method is to prepare quantum dot ink by modifying BaTiO3 nanocrystals with a silane coupling agent, spin-coating it on the surface of a P-type silicon wafer cleaned by RCA to form a quantum dot array, and then activate it in a solution containing copper sulfate and trisodium citrate under the assistance of ultrasound. Then, in a microfluidic reaction chamber, chemical copper plating is carried out using an alkaline plating solution containing copper sulfate, disodium ethylenediaminetetraacetic acid and glyoxylic acid under the assistance of ultrasound and laser. Finally, the silicon wafer with a copper surface is rinsed with deionized water and ethanol and blown dry with nitrogen.
2. The chemical plating method according to claim 1, wherein The following steps are involved: S1. Preparation of quantum dot ink: BaTiO3 nanocrystals were dispersed in ethanol, (3-aminopropyl)triethoxysilane was added, stirred for reaction, washed, and dried to obtain modified BaTiO3 quantum dots, which were then dispersed in isopropanol, a surfactant was added, and ultrasonication was performed to obtain quantum dot ink; S2. Preparation of quantum dot array: Take a single crystal silicon wafer, perform standard RCA cleaning, apply quantum dot ink to the treated silicon wafer surface by spin coating, and dry it to obtain a quantum dot array; S3. Silicon wafer activation: A silicon wafer with a quantum dot array is fixed in a reaction tank, immersed in an activation solution, and subjected to high-frequency ultrasonic waves to produce an activated silicon wafer. S4. Copper film preparation: The activated silicon wafer is transferred to a reaction chamber, and a plating solution is supplied via a syringe pump. Ultrasonic waves and a laser array are simultaneously applied to continuously electrolessly plate copper to form a copper film. S5. Post-processing: Rinse the silicon wafer with deionized water, then rinse with anhydrous ethanol, and finally blow dry with high-purity nitrogen to obtain a silicon wafer with a copper-plated surface.
3. The chemical plating method according to claim 2, wherein: In the S1, the average particle size of the BaTiO3 nanocrystals is 50 nm, the mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals is 1:10, the stirring reaction is carried out at 60°C for 4 hours, and the drying is carried out at 60°C under vacuum conditions for 2 hours. The concentration of the modified BaTiO3 quantum dots in isopropanol is 0.5 mg / mL, the ultrasonic power is 100 W, and the time is 15 minutes. The surfactant is octylphenol polyoxyethylene ether, and the concentration in isopropanol is 0.01% v / v.
4. The chemical plating method according to claim 2, wherein: In the S2, the single crystal silicon wafer is a P-type with a resistivity of 1-10Ω·cm. <100> For single crystal silicon wafers, the amount of quantum dot ink used was 0.2 mL, and drying was performed in an oven at 80°C for 10 minutes.
5. The chemical plating method according to claim 2, wherein: In S2, the spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage.
6. The chemical plating method according to claim 2, wherein: In S2, the standard RCA cleaning method includes: SC-1 cleaning, SC-2 cleaning, and hydrogen peroxide treatment; The SC-1 cleaning solution composition is NH4OH:H2O2:H2O=1:1:5, and the cleaning is carried out at 70-80°C for 10 minutes; The SC-2 cleaning solution composition is HCl:H2O2:H2O=1:1:6, and the cleaning is carried out at 70-80°C for 10 minutes; The hydrogen peroxide treatment uses a 10% hydrogen peroxide aqueous solution at 80° C. for 30 minutes.
7. The chemical plating method according to claim 2, wherein: In S3, the temperature of the activation solution was maintained at 25°C, the frequency of the ultrasonic transducer was 1.0 MHz, and the sound intensity was 0.5 W / cm 2 , ultrasonic treatment time was 15 min; The activation solution components include copper sulfate and trisodium citrate, wherein the concentration of copper sulfate is 0.01M, the concentration of trisodium citrate is 0.05M, and the pH value is 4.8-5.
2.
8. The chemical plating method according to claim 2, wherein: In the S4, the reaction temperature is 58-62°C, the reaction chamber is provided with a microfluidic channel, the liquid is supplied in a pulsed manner, the pulse width is 0.5 seconds, the pulse interval is 2.0 seconds, the flow rate is 5 mL / min, the ultrasonic frequency is 40 kHz, the power is 50 W, the wavelength of the laser array is 532 nm, and the laser power density is 50 mW / cm 2 , the chemical copper plating time is 60 minutes.
9. The chemical plating method according to claim 2, wherein: In S4, the components of the chemical copper plating solution include copper sulfate, disodium edetate, glyoxylic acid, a stabilizer and a surfactant, wherein the concentration of copper sulfate is 0.08 M, the concentration of disodium edetate is 0.15 M, the pH value is 12.3-12.7, the concentration of glyoxylic acid is 0.10 M, the stabilizer is 2-mercaptobenzothiazole, the concentration is 2 ppm, and the surfactant is polyethylene glycol octylphenyl ether, the concentration is 50 ppm.
10. The chemical plating method according to claim 2, wherein: The specific steps include: S1. Preparation of quantum dot ink: BaTiO3 nanocrystals with an average particle size of 50 nm were dispersed in ethanol, and (3-aminopropyl)triethoxysilane was added at a mass ratio of (3-aminopropyl)triethoxysilane to BaTiO3 nanocrystals of 1:
10. The mixture was stirred at 60°C for 4 hours, washed multiple times with ethanol, and vacuum-dried at 60°C for 2 hours to obtain modified BaTiO3 quantum dots. The modified BaTiO3 quantum dots were then dispersed in isopropanol to a concentration of 0.5 mg / mL. The surfactant octylphenol polyoxyethylene ether was added to a concentration of 0.01% v / v, and ultrasonicated at 100 W for 15 minutes to prepare quantum dot ink. S2. Preparation of quantum dot array: Take P-type with a resistivity of 1-10Ω·cm <100> Single crystal silicon wafers were cleaned using a standard RCA cleaning method. The cleaned silicon wafers were placed in a 10% hydrogen peroxide solution and treated at 80°C for 30 minutes. The wafers were then rinsed with deionized water and dried with nitrogen to obtain the treated silicon wafers. Quantum dot ink was then applied to the treated silicon wafer surface using a spin coating method. 0.2 mL of quantum dot ink was added to the center of the wafer. The spin coating parameters were 500 rpm for 10 seconds in the first stage and 3000 rpm for 40 seconds in the second stage. The wafers were then dried in an 80°C oven for 10 minutes to obtain quantum dot arrays. The standard RCA cleaning method is as follows: SC-1 cleaning: NH4OH:H2O2:H2O=1:1:5, cleaning at 70-80℃ for 10 minutes, rinsing with deionized water; SC-2 cleaning: HCl:H2O2:H2O=1:1:6, cleaning at 70-80℃ for 10 minutes, rinsing with deionized water, and drying with nitrogen; S3. Silicon wafer activation: The silicon wafer with the quantum dot array was fixed in a reaction tank and immersed in the activation solution. The solution temperature was maintained at 25°C. High-frequency ultrasound was applied to the bottom or side wall of the reaction tank. The ultrasonic transducer frequency was 1.0 MHz and the sound intensity was 0.5 W / cm 2 , continue ultrasonic treatment for 15 minutes to obtain activated silicon wafers; The activation solution comprises the following components: copper sulfate concentration 0.01M, trisodium citrate concentration 0.05M, and the pH is adjusted to 4.8-5.2 with dilute sulfuric acid or dilute sodium hydroxide; S4. Preparation of copper film: Transfer the activated silicon wafer to a reaction chamber with a microfluidic channel at 58-62°C. Pulse the plating solution via a syringe pump with a pulse width of 0.5 s, a pulse interval of 2.0 s, and a flow rate of 5 mL / min. Simultaneously, apply ultrasound and a laser array with an ultrasound frequency of 40 kHz and a power of 50 W. The wavelength of the laser array is 532 nm, and the laser power density is controlled at 50 mW / cm 2 , continuing chemical copper plating for 60 minutes to obtain a copper film; The composition of the electroless copper plating solution is as follows: 0.08M copper sulfate, 0.15M disodium ethylenediaminetetraacetic acid, pH adjusted to 12.3-12.7 with sodium hydroxide, 0.10M glyoxylic acid, 2ppm stabilizer 2-mercaptobenzothiazole, 50ppm surfactant polyethylene glycol octylphenyl ether; S5. Post-processing: After the chemical copper plating is completed, the silicon wafer is immediately rinsed with deionized water for 3 minutes, then rinsed with anhydrous ethanol for 1 minute, and finally blown dry with high-purity nitrogen to obtain a silicon wafer with a copper-plated surface.
Citation Information
Cited By
Nano-molecular device magnetic response modeling method and system based on machine learning
CN120822425A